1999
DOI: 10.1093/carcin/20.10.1985
|View full text |Cite
|
Sign up to set email alerts
|

Decreased 13-S-hydroxyoctadecadienoic acid levels and 15-lipoxygenase-1 expression in human colon cancers

Abstract: 13-S-Hydroxyoctadecadienoic acid (13-S-HODE), the product of 15-lipoxygenase (15-LOX) metabolism of linoleic acid, enhances cellular mitogenic responses to certain growth factors. Other observations have questioned whether 13-S-HODE has tumorigenic effects. Our study evaluated the hypothesis that 15-LOX-1 is overexpressed in colon cancers resulting in an increase in intracellular 13-S-HODE. 15-LOX-1 and 13-S-HODE were quantified using western blots, ELISA and immunohistochemistry in 18 human colon cancers with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
121
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 141 publications
(129 citation statements)
references
References 29 publications
8
121
0
Order By: Relevance
“…Chen et al (32) found that the concentration of 15(S)-HETE in serum was ϳ60% lower in patients with colon cancer compared with normal patients. Our results are consistent with those reported by Shureiqi et al (35) and Chen et al (32), and with the hypothesis that loss of 15-LOX-1 expression favors malignant progression in colon tissue (17,34,39,35,32). For instance, loss of 15-LOX-1 would nullify its regulation of TrxR, the G 1 cell cycle checkpoint, and BAX expression.…”
supporting
confidence: 93%
See 2 more Smart Citations
“…Chen et al (32) found that the concentration of 15(S)-HETE in serum was ϳ60% lower in patients with colon cancer compared with normal patients. Our results are consistent with those reported by Shureiqi et al (35) and Chen et al (32), and with the hypothesis that loss of 15-LOX-1 expression favors malignant progression in colon tissue (17,34,39,35,32). For instance, loss of 15-LOX-1 would nullify its regulation of TrxR, the G 1 cell cycle checkpoint, and BAX expression.…”
supporting
confidence: 93%
“…Ikawa et al (50) found elevated expression of 15-LOX-1 in ϳ 60% (13/21) of colon tumors. In contrast, Shureiqi et al (35) found lower levels of 13(S)-HODE in 15/18 (ϳ 83%) colon tumors compared with normal tissue. Chen et al (32) found that the concentration of 15(S)-HETE in serum was ϳ60% lower in patients with colon cancer compared with normal patients.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…Determination of 13-HODE Levels by ELISA (19,20)-13-HODE was extracted from each sample at 4°C as follows. The solution was acidified to a pH of 3.5-4.0.…”
Section: Methodsmentioning
confidence: 99%
“…Restoring apoptosis is an important anticarcinogenic mechanism (2,4,5). Loss of apoptosis in colorectal cancer cells is linked to down-regulation in 15-lipoxygenase-1 (15-LOX-1) expression, and the primary product of 15-LOX-1 acting on linoleic acid, 13-S-hydroxyoctadecadienoic acid (13-S-HODE) (6), restores apoptosis in colorectal cancer cells (7). Nonsteroidal antiinf lammator y drugs (NSAIDs) induce apoptosis in colorectal cancer cells (8)(9)(10).…”
mentioning
confidence: 99%